Biosorption/Precipitation of Heavy Metals by Partially Degraded Keratin/Soluble Peptides/Amino Acids By-Products of Degradation of Human Hair by Keratinase Isolated from Alcaligenes Faecalis Strain AIR10 - Obinna, Ezenwali Moses (Bumi Publikasi Nusantara, 2023)
This research involves a systematic process to reduce the effects of heavy metals on health and the environment through the metabolism of human hair. In this study, the by-product of the breakdown of microbial keratinase was keratin; free amino acids and partially degraded peptide/keratin were used as precipitates and adsorbents, respectively, to remove Copper (Cu), Iron (Fe), Nickel (Ni), Zinc (Zn) Cobalt (Co) and Lead (Pb) from pollution. Atomic absorption spectrophotometry is used to measure metal concentrations. Degraded human hair was an efficient but insignificant weight absorber compared to untreated human hair, achieving almost 85.81±0.0077% adsorption for chloride. Our data show that alkaline pH favors lead acetate deposited by the supernatant over neutral and acidic regions. Both treated and untreated human hair showed a significant percentage of ZnSO4 and NiCl2 biosorption, with CuSO4 showing the percentage of precipitation, the lowest percentage of biosorption. Our SEM results suggest that a technology may be required to increase the surface area of treated human hair to increase the adsorption capacity.